Characterization of D-Allulose-3-Epimerase From Ruminiclostridium papyrosolvens and Immobilization Within Metal-Organic Frameworks - Yang, Jiaming; Fan, Dexun; Zhao, Fengguang; Lin, Ying; Zheng, Suiping; Han, Shuangyan (Frontiers in Bioengineering and Biotechnology, 2022)
D-allulose is one sort of C-3 epimer of D-fructose with low calorie (0.4 kcal/g) and high sweetness (70% of the relative sweetness of sucrose), which can be biosynthesis by D-allulose-3-epimerase (DAE). In this work, we report the characterization of a novel DAE from Ruminiclostridium papyrosolvens (RpDAE) by genome mining approach. The activity of RpDAE reached maximum activity at pH 7.5 and 60 °C, supplement with 1 mM Co2+. Using 500 g/L D-fructose as substrate for epimerization reaction, RpDAE produced 149.5 g/L D-allulose. In addition, RpDAE was immobilized within the microporous zeolite imidazolate framework, ZIF67, by in situ encapsulation at room temperature. The synthesized bio-composite was characterized by powder X-ray diffraction and fourier transform infrared spectroscopy. RpDAE-ZIF67 maintained 56% of residual activity after six progressive cycles of reuse. This study provides useful guidance for further engineering applications and realizing the industrial production of D-allulose.